Az Uniós finanszírozási források és a Kkv-szektor teljesítménymutatóinak összefüggései - Gyurcsik, Petronella (Közép-Európai Közlemények, 2017)
Recognising the key role of small and medium-sized enterprises in the economy and society, supporting, expanding or financing the SME sector is a key issue of today’s economic policy both on national and EU level. In addition to recognising the importance of the sector, the anomaly of access to funds owing to differences between SMEs and large companies has become obvious. The aim of this study is to examine the national economic effect of development and growth generated by various EU measures on the most significant performance indicators of enterprises though the analysis of time series, map the types and alternatives of different EU funds and capital injections offered with the purpose of improving the capital situation of SMEs, as well as to describe the character of nonfinancial aids. My theoretical research, which comprises the positive effects as well as the drawbacks of financial aids, is primarily based on the relevant EU directives, calls, calls for tender, previous studies and literature.